Aiming at Doves: Experimental Evidence of Military Images' Political Effects. (August 2017) - Caverley, Jonathan D.; Krupnikov, Yanna
Politicians (and journalists covering them) assume that association with the military has political consequences. We propose and experimentally test conditions under which military images have such effects. We presented subjects with images of the US president before varying backgrounds—including soldiers, students, children, and "ordinary" people. Only the image of soldiers has any significant effect, shifting participant preferences toward spending money on defense over education. The image does this by increasing respondent sense of threats to national security, despite the military's depiction out of combat and in the background. The soldiers image does little to shift opinion about the president. However, the image has the largest hawkish effect on both the president's copartisans and the strongest supporters. Given the routine use by many democracies of tactics unlikely to produce images of one's fellow citizens in combat, the power of more sanitized images to cue hawkish policy preferences requires increased attention.